Удосконалення технології м'ясних продуктів з використанням м'яса перепелів - Аль-Хашімі, Хайдер Мохаммед Тахер (My University, 2019)
У дисертаційній роботі викладено результати досліджень щодо удосконалення технологій м'ясних виробів з використанням м'яса перепелів. Уперше досліджено гістологічні та анатомічні показники білого і червоного м'яса перепелів, парного, охолодженого, замороженого, при відгодівлі самців японської породи до 42 денного віку. Досліджено вплив заморожування на мікроструктурні зміни в м'ясі перепелів. В процесі заморожування в м'ясі спостерігалося зменшення діаметра м'язових волокон в області грудки на 15,6-29,2 % і стегна – на 13,9-27,1 %, а також їх кількості на 14,2-20,3 % і 4,8-19,1 % відповідно. Внаслідок чого зменшуються розміри структурних елементів – м'язових пучків 1 порядку. Найменші зміни в структурі скелетної м'язової тканини відзначені у парного і охолодженого м'яса перепелів, найбільші – при заморожуванні остиглого м'яса. Удосконалено технологію підготовки м'яса перепелів для їх промислового використання. Підібрані і змодельовані оптимальні варіанти розсолів систем для підвищення технологічних характеристик м'яса перепелів при посолі. Розроблено рецептурні склади розсолів з тваринами і комбінованими білками. Вивчено їх вплив на функціонально-технологічні властивості готових виробів. Досліджено можливості комбінування м'яса перепелів з харчовими інгредієнтами – соусом бальзамік, рисом, морквою, цибулею, перепелиними і курячими яйцями для підвищення технологічних характеристик готових виробів. Вивчено вплив теплової обробки на технологічні і структурно-технологічні характеристики м'яса перепелів. У процесі варіння виробів при температурі 75˚ С характеристики готового продукту були краще, ніж при 85˚ С, що свідчить про позитивний вплив даної температури варіння на якісні властивості готового продукту. Вдосконалено технологію підготовки м'яса перепелів для їх промислового використання. Розроблено раціональні рецептури копчено-варених, запечених виробів і консервів з м'яса перепелів, збалансованих за амінокислотним складом. Удосконалено технології, технологічні схеми виробництва копчено-варених, запечених продуктів та консервів з м'яса перепелів. In dissertation work the results of researches on improvement of technologies of meat products with use of quail meat are presented. On the basis of analysis of poultry raw materials, rational directions of quail meat usage in technologies of food products are justified, technologies of baked, smoked and boiled, and sterilized meat products with the usage of quail meat are improved and scientifically based. The technologies could be used in meat processing industry of Ukraine and Iraq. The results show the practical meaning for expanding of the assortment of the products, based on quail meat with long and short selling period, increase efficiency of the usage of this raw material for provision of the population with a high-quality frozen quail meat and food products of quail meat. For the first time histological and anatomical indices of white and red quail meat, paired, chilled, frozen, with fattening males of the Japanese breed up to 42 days of age were investigated. The effect of freezing on microstructural changes in quail meat is investigated. In the process of freezing in meat, there was a decrease in the diameter of muscle fibers in the breast region by 15.6-29,2 % and the thighs - by 13,9-27,1 %, as well as their number by 14,2-20,3 % and 4,8-19,1 % respectively. As a result, the size of structural elements - muscle beams of 1 order decreases. The slightest changes in the structure of skeletal muscle tissue are noted in paired and chilled quail meat, the largest - when frozen meat. The technology of preparation of quail meat for their industrial use is improved. Selected and simulated optimal variants of brine systems for improving the technological characteristics of quail meat with salt. Recipe formulations of brines with animals and combined proteins have been developed. Their influence on functional and technological properties of finished products is studied. Comparative characteristics of the influence of syringe pickle of combined composition with the usage of animal and vegetable proteins and cellulose on technological indicators of broiler meat and quail meat of Japanese breed “Pharaoh” is given, which allowed to reveal the effects of synergistic use of ingredients, as part of brines, for promotion of functional and technological indicators of smoked-cooked products of the quail meat. The possibilities of combining quail meat with food ingredients - balsamic, rice, carrots, onions, quail and chicken eggs for improving the technological characteristics of finished products have been explored. The effectiveness of applying the developed balsamic sauce with spices in the amount of 1-4% of the mass of meat for improving sensory indicators of baked quail was confirmed. Developed technologies of getting the balsamic sauce and its appliance for quail meat baking are protected with utility patent. A new data on the influence of combining animal and vegetable proteins in raw meat for technologies of baked, smoked-cooked and sterilized meat products with the usage of quail meat on the possibility of their biological and food value increasing and regulating functional and technological, and structural and mechanical indicators during optimization modeling of heat treatment modes was received. The influence of heat treatment on technological and structural-technological characteristics of quail meat was studied. In the process of cooking products at a temperature of 75 ° C the characteristics of the finished product were better than at 85 ° C, which indicates the positive effect of this cooking temperature on the qualitative properties of the finished product. It is scientifically justified that for getting an optimal structural and mechanical, and sensory characteristics of the sterilized quail meat of the 42nd fattening day, sterilization of the canned goods with net mass 480g should be conducted with the temperature of 115°C not less than 5400 seconds. The technology of preparation of quail meat for their industrial use is improved. The rational formulations of smoked-boiled, baked products and canned meat from quail, balanced on the amino acid prescriptions were developed. Technologies, technological schemes of manufacture of smoked-boiled, baked products and canned meat from quail are improved.
Keywords: перепели; яєчна та м’ясна продуктивність; рецептура; посол; соус бальзамік; комбіновані білки; технологія; quail; egg and meat productivity; compounding; ambassador; balsamic; combined proteins; technology